2016
DOI: 10.1182/blood-2015-06-648667
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric chronic myeloid leukemia is a unique disease that requires a different approach

Abstract: Chronic myelogenous leukemia (CML) in children is relatively rare. Because of a lack of robust clinical study evidence, management of CML in children is not standardized and often follows guidelines developed for adults. Children and young adults tend to have a more aggressive clinical presentation than older adults, and prognostic scores for adult CML do not apply to children. CML in children has been considered to have the same biology as in adults, but recent data indicate that some genetic differences exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
176
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 101 publications
3
176
2
5
Order By: Relevance
“…Overall, there was a slightly higher fraction of pediatric patients achieving MR4 already during the initial decline (3 of 40 children vs. 1 of 69 adults). Although several studies suggest that initial response to imatinib treatment was inferior in e13a2 patients, 3 we found no statistically relevant differences in treatment response between patients harboring the e13a2 and the e14a2 phenotype of CML. However, given the small sample size (which is approx.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…Overall, there was a slightly higher fraction of pediatric patients achieving MR4 already during the initial decline (3 of 40 children vs. 1 of 69 adults). Although several studies suggest that initial response to imatinib treatment was inferior in e13a2 patients, 3 we found no statistically relevant differences in treatment response between patients harboring the e13a2 and the e14a2 phenotype of CML. However, given the small sample size (which is approx.…”
contrasting
confidence: 47%
“…2 However, CML is rare in cohorts of patients under 20 years of age, and data on the kinetics of the BCR-ABL1 expression in response to TKI treatment in children and teenagers are still scarce. While it is widely agreed that the cellular and molecular features of CML in children are identical to adults, it must be remembered that the host is still a growing organism, 3 and initial tumor cell burden and treatment responses may vary according to age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though CML pediatric and adult population share the same fusion gene BCR-ABL, Krumbholz, et al have shown that breakpoint distribution in BCR in children is different than adult (2). Besides pediatric CML compared to adult one is described as more aggressive (3). Imatinib is, as in adults, an effective first line treatment in children and adolescents with CML (1).…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день в лечении ХМЛ у детей опираются на данные, полученные при лечении взрослых пациентов, хотя резонно предположить, что ХМЛ у 2-летнего ребенка имеет отличную биологию по сравнению с заболеванием у пожилого пациента. Вероятно, особенности быстро растущего и развиваю-щегося детского организма могут оказывать влияние на течение ХМЛ, прогноз заболевания, ответ на терапию и развитие побочных эффектов терапии [4].…”
Section: Discussionunclassified